PENGEMBANGAN POLA LATIHAN INBOUND MENGGUNAKAN MEDIA VIDEO PADA KEGIATAN EKSTRAKURIKULER BOLABASKET SMP NEGERI 15 MALANG - Robby Kurniawan; Siti Nurrochmah; Oni Bagus Januarto (Jurnal Pendidikan Jasmani)
bstract: basketball extracurricular activities useful to develop talents and skills of trainees. In result of the needs analysis found that problems arise, among others: (1) the pattern of inbound given training is hard to accept trainees, (2) trainers and trainees need video media and inbound exercise patterns corresponding characteristics of trainees. This research aims to develop inbound exercise pattern that is packaged using video media according to the characteristics of trainees. This study uses a conceptual model based on the operational theory or principles validated. Based on trial results showed 87.50% of small groups of 10 participants and a large group test showed 88.75% of the 30 participants.Key words: Exercise Pattern, Inbound Basketball, Media Video